Phytomelatonin: An overview of the importance and mediating functions of melatonin against environmental stresses. Issue 2 (18th November 2020) - Altaf, Muhammad Ahsan; Shahid, Rabia; Ren, Ming‐Xun; Mora‐Poblete, Freddy; Arnao, Marino B.; Naz, Safina; Anwar, Muhammad; Altaf, Muhammad Mohsin; Shahid, Sidra; Shakoor, Awais; Sohail, Hamza; Ahmar, Sunny; et al.
Abstract: Recently, melatonin has gained significant importance in plant research. The presence of melatonin in the plant kingdom has been known since 1995. It is a molecule that is conserved in a wide array of evolutionary distant organisms. Its functions and characteristics have been found to be similar in both plants and animals. The review focuses on the role of melatonin pertaining to physiological functions in higher plants. Melatonin regulates physiological functions regarding auxin activity, root, shoot, and explant growth, activates germination of seeds, promotes rhizogenesis (growth of adventitious and lateral roots), and holds up impelled leaf senescence. Melatonin is a natural bio‐stimulant that creates resistance in field crops against various abiotic stress, including heat, chemical pollutants, cold, drought, salinity, and harmful ultra‐violet radiation. The full potential of melatonin in regulating physiological functions in higher plants still needs to be explored by further research.